PENGARUH PUJIAN TERHADAP PRESTASI BELAJAR MATEMATIKA PADA SISWA KELAS 4 SEKOLAH DASAR - Muslimah Zahro Romas (LPPM Universitas Proklamasi 45, 2006)
Praising students genuinely for demonstrating high efforts in studying math will increase their scores in math. Twenty two students, 9-10 years old, grade fourth, participate in this experiment. Half students are in the experiment group whilst the rests are in the control group, on the basis of the random assignment principle. The F = 24.990 p = .000 and the t = 5.632 p = .000 demonstrate that praising students has increased their math scores. Some suggestions in adding some variables such as student's gender are discussed with intention to improve this study.